Optimization of Energy and Time Variations for Synthesis of N doped TiO2 Nanotube using Microwave-Asssisted Hydrothermal Method - Cindy Candrika Anugrahayu; Cahyorini Kusumawardani (Universitas Negeri Yogyakarta, 2021)
This study aimed to determine the effect of energy and time hydrothermal microwave time variations on the crystal structure and N-TiO2 nanotube photocatalytic activity. The synthesis of N-TiO2 nanotube was performed with the hydrothermal microwave method. The N-TiO2 preparationwas carried out by dissolving ethylenediamine precursor in 80 ml of 96% ethanol and 3 ml TTIP which was reacted at 70 °C for 4 hours. The obtained N-TiO2 was formed into nanotubes used the hydrotermal microwave method in low temperature (180W), medium temperature (360 W), and high temperature (720 W) with time variations of 30 minutes, 1 hour, and 2 hours. The microwave hydrothermal process in this study used 10 M NaOH to form a tubular structure and 0.5 M HCl as an ion exchange. The characterization analysis performed by X-Ray Diffraction, UV-Diffuse Reflectance Spectroscopy, and blue methylene degradation. The results of this study indicate that the variations of time and energy of the microwave hydrothermal method affect the crystal structure of the N-TiO2 nanotubes. The nanotubes structure has been formed at a variety of low energy 2 hours, medium energy 0.5 hours, 1 hour and 2 hours, and high energy 2 hours. Energy and time variations of hydrothermal microwave affect the photocatalytic activity of N-TiO2 nanotubes showed second-order kinetics. The best percentage of degradation produced in the T2 variation is the photocatalyst reaction of 71.89% and the adsorbs reaction of 64.81%.